What do organizational leaders need from lean graduate programming - Flumerfelt, Shannon (2016)
Purpose – This paper aims to assess the needs for a lean continuous improvement professional certificate and/or lean leadership cognate for a Doctorate of Education in leadership focused in three main research questions: “What do organizational leaders need from a Lean graduate programming?”; “What are the preferable methods of delivery for Lean teaching/learning?” and “What are the main learner outcomes and do how these impact organizational and continuous improvement outcomes?” Design/methodology/approach – A survey to 37 organizational leaders in a North-American state was conducted via telephone and email that were returned to the researcher. The survey was designed to target a solid cross-section of organizational decision makers in regard to the need for and type of lean training desired, if at all, for employees. Using a mixed methods approach, the survey was designed to collect both qualitative and quantitative information. Findings – Respondents indicated that lean continuous improvement thinking and lean processproject management were most the desirable content options. The method of delivery was not as clear with on-ground and online relying on job-embedded, project-based methods as most desirable approaches. Learner outcomes of mastery of lean content along with the ability to impact organizational and continuous improvement outcomes were favored. Originality/value – Lean leadership education is valued learning by organizational leaders. As so, higher education institutions must be aware of matching better organizational needs with learning experiences. This paper presents a survey that intended to do this in an original way.